2010
DOI: 10.1002/cjce.20257
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state for gaseous nitrogen determined from isotropic model potentials

Abstract: A four-term virial equation of state was combined with isotropic potential models to predict accurate volumetric and caloric thermodynamic properties of nitrogen in the gas phase. The parameters of the model potentials were determined from a fit to acoustic data alone; no other data was used. For nitrogen, it was only necessary to approximate the fourth virial coefficient at the level of interactions that contained no more than one triplet potential; higher order approximations offered no further advantage. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Values of the perfect-gas heat capacity required to calculate acoustic virial coe±cients were determined as in Ref. 10. Figure 1 compares values of B calculated in this way with the experimental data of several authors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Values of the perfect-gas heat capacity required to calculate acoustic virial coe±cients were determined as in Ref. 10. Figure 1 compares values of B calculated in this way with the experimental data of several authors.…”
Section: Resultsmentioning
confidence: 99%
“…(17) the three-body strength coe±cient for nitrogen was required; for this, we used the value # 123 /k ¼ 0:001 K nm 9 which was suggested by results from previous work. 10 The application of Eq. (8) requires knowledge of the quadrupole moment for nitrogen; for this, the value  ffiffiffi k p ¼ À0:396 (K nm 5 Þ 1=2 reported by Hurt and Bose 24 was used.…”
Section: Potential Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…We strongly discourage from its use, particularly as correct parametrizations for fourth- [14] and higher-order [18] virial EOS for Argon have been reported recently. We also discourage from employing ad hoc ''approximations'' [7,[10][11][12][13] to the 3-body or, generally, the non-additive contributions to D, and have shown that such ''approximations'' may, in fact, overestimate these contributions significantly. We consequently disagree with Ref.…”
mentioning
confidence: 95%
“…[1] -similarly to elsewhere [10][11][12] and to Trusler [13] -cites diagrammatic works of Casanova et al [6] and Dulla et al [7], neither justify to discard products of f ijk 's in any other than an ad hoc fashion.…”
mentioning
confidence: 96%